The New Era of mRNA Vaccines: The Success of the COVID-19 Vaccines and the Safety Concerns in Adolescents - Muthu Gopal; Anusiga S. Rajan; Kavita Vasudevan; Ashwani Kumar; Vijesh S. Kuttiatt (Indian Journal of Community Medicine)
A remarkable scientific achievement during the Covid pandemic is the rapid development and deployment of the mRNA vaccines which played a crucial role in reducing the Covid-related morbidity and mortality. The first-time safe use of the mRNA vaccine platform in humans opened up a new era in vaccinology. In the near future, the mRNA vaccine platform is likely to be used for other diseases as well. Though the Covid mRNA vaccine has been found to be safe in children, a matter of concern is the rare adverse event myocarditis, which was mostly observed among male adolescents. In this setting, we briefly discuss mRNA vaccine-related myocarditis and suggest that the safety concerns need to be alleviated by larger studies with long-term follow-up. We also stress the need for the generation of safety data from children in lower- and middle-income countries as there is limited experience with mRNA vaccines in such settings. The underlying mechanisms need to be understood well as the mRNA vaccine platform holds enormous promise for the future development of vaccines for several diseases.